A SISTEM PENANDA WAKTU AKTIVITAS KEGIATAN BINTARA MAHASISWA POLTEKAD MENGGUNAKAN RTC BERBASIS ATMEGA328: PENANDA WAKTU AKTIVITAS MENGGUNAKAN RTC BERBASIS ATMEGA328 - Tri Wicaksono, Agung; widiatmoko, dekki; Walid, Mitahul (Pustaka Poltekad, 2024)
This research aims to develop an activity time marking system specifically designed for the daily activities of Poltekad Student Non-Commissioned Officers such as prayer times, meal times, sports roll call times and checking roll times, using an ATmega328 microcontroller. This system will use an RTC (Real-Time Clock) module to maintain accurate time and provide notifications via sound notification or alarm. By utilizing assistive technology, this system will help users remember and organize their various daily activities. Microcontroller programming and hardware interfacing are an integral part of the development of this system, which is expected to increase accessibility and timeliness when carrying out an activity.